2019
DOI: 10.1038/s41467-019-12872-5
|View full text |Cite
|
Sign up to set email alerts
|

Molecular determinants of nephron vascular specialization in the kidney

Abstract: Although kidney parenchymal tissue can be generated in vitro, reconstructing the complex vasculature of the kidney remains a daunting task. The molecular pathways that specify and sustain functional, phenotypic and structural heterogeneity of the kidney vasculature are unknown. Here, we employ high-throughput bulk and single-cell RNA sequencing of the non-lymphatic endothelial cells (ECs) of the kidney to identify the molecular pathways that dictate vascular zonation from embryos to adulthood. We show that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
107
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 109 publications
(113 citation statements)
references
References 54 publications
6
107
0
Order By: Relevance
“…Endothelial cell heterogeneity has been reported in macro- and microvascular beds of different organs 30 , 31 , including the kidney 32 and human cancers 33 . In an elegant study, Barry et al demonstrated that kidney vascular heterogeneity diversifies perinatally and throughout adulthood 32 . Recently, evidence for intraglomerular heterogeneity of endothelial cells has emerged.…”
Section: Discussionmentioning
confidence: 99%
“…Endothelial cell heterogeneity has been reported in macro- and microvascular beds of different organs 30 , 31 , including the kidney 32 and human cancers 33 . In an elegant study, Barry et al demonstrated that kidney vascular heterogeneity diversifies perinatally and throughout adulthood 32 . Recently, evidence for intraglomerular heterogeneity of endothelial cells has emerged.…”
Section: Discussionmentioning
confidence: 99%
“…1b ). Concomitantly, we observed restricted expression of known organotypic EC markers in each of the remaining groups: Gata4 expression was increased in liver ECs 25 , Sftpd was enriched in lung ECs 49 , Rbp7 was most highly expressed in heart ECs 50 , 51 , and kidney ECs were the only group expressing Slc14a1 52 (Supplementary Fig. 1b ).…”
Section: Resultsmentioning
confidence: 78%
“…By means of bulk transcriptomic analyses, we contrasted the vascular beds of the bone marrow and the liver as well as those of non-hematopoietic organs such as the lungs, heart, and kidneys. These analyses yielded unique transcriptomic signatures for each of the organs assayed that were characterized by overrepresentation of known markers such as Gata4 25 in the liver and Slc14a1 in the kidneys 52 . In addition, we found that Jak3 expression was uniquely enriched in the bone marrow vascular bed.…”
Section: Discussionmentioning
confidence: 99%
“…All vascular EC originate in the embryonic mesoderm (Dyer and Patterson, 2010), however, they display remarkable organspecific characteristics and genetic programming, leading to specialization in morphology, such as fenestrations, and functionality, such as cell-cell interaction and permeability (Chi et al, 2003;Nolan et al, 2013). EC differentiation relies on both epigenetic mechanisms and the interaction with the microenvironment, determining the existence of different subtypes of EC even within the same vascular bed (Kusumbe et al, 2014;Ramasamy, 2017;Barry et al, 2019). For example, two subpopulations of EC have been characterized in the murine skeletal system; the H type, which are responsible for angiogenesis, and the L type, which form the sinusoidal capillaries in bones (Kusumbe et al, 2014).…”
Section: Heterogeneity Of Endothelial Cellsmentioning
confidence: 99%